2021
DOI: 10.1073/pnas.2021793118
|View full text |Cite
|
Sign up to set email alerts
|

Collectivism predicts mask use during COVID-19

Abstract: Since its outbreak, COVID-19 has impacted world regions differentially. Whereas some regions still record tens of thousands of new infections daily, other regions have contained the virus. What explains these striking regional differences? We advance a cultural psychological perspective on mask usage, a precautionary measure vital for curbing the pandemic. Four large-scale studies provide evidence that collectivism (versus individualism) positively predicts mask usage—both within the United States and across t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
225
4
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(244 citation statements)
references
References 54 publications
11
225
4
4
Order By: Relevance
“…While the role of nationalism might be specific to the Chinese context, the Chinese situation is not a complete separation from other parts of the world. A recent study identified that collectivism predicts mask use during the COVID-19 pandemic in the United States and worldwide [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the role of nationalism might be specific to the Chinese context, the Chinese situation is not a complete separation from other parts of the world. A recent study identified that collectivism predicts mask use during the COVID-19 pandemic in the United States and worldwide [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies showed the prevalence of self-interest bias across various unethical behaviors and normative misconducts (e.g., Bocian & Wojciszke, 2014;Weiss et al, 2018), self-interest bias may not be a "one-fits-all" rule for all COVID-19-related self-serving acts. And different COVID-19-related self-serving behaviors (e.g., resisting mask usage, Lu et al, 2021;hoarding, Columbus, 2021) may be scrutinized given their unique socio-psychological implications. Therefore, future research may (1) examine the cultural differences on self-interest bias in other morally relevant domains and more countries, and (2) directly investigate the mechanisms underlying these differences.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Early evidence of COVID-19 self-reported behavior lend credence to the notion of the importance of social obligations; in survey studies of adolescents, one's perceived social responsibility to others was positively related to engagement in preventative behaviors . Further, recent studies have documented that those collectivism was related to greater intentions to reduce the spread of the virus (Biddlestone et al, 2020), don masks (Lu et al, 2021), and reduce mobility in response to COVID-19 (Im and Chen, 2020). Thus, cultural collectivism across the United States may also account for greater and prolonged reduction in mobility compared to their more individualistic counterparts.…”
Section: Social and Cultural Values And Social Distancingmentioning
confidence: 99%